President's Annual Report, 1964-1965 - Thaxton, J. Ralph, Dr. (Valdosta State University Archives and Special Collections, 1965)
The President's Annual Report to the Georgia Board of Regents for the fiscal year 1964-1965 for Valdosta State College. Topics include new hires, integration, sports, religious activities on campus, and faculty research. With record breaking student enrollments, Valdosta State College is growing faster than it is expanding physically. The Physics department is separated from the Mathematics department, dorm rooms are filled to capacity, and the library is being expanded to facilitate demand.
Presidents Annual Report, 1964-1965
Keywords: Valdosta State University; College publications; Corporate reports; College presidents